A regra e o jogo: identidade, hegemonia e politicas públicas para as culturas populares no Brasil contemporâneo - Machado, Henry Alexandre Durante (Universidade de São Paulo | Escola de Comunicações e Artes, 2019)
This work aims to investigate the relationship between the dynamics of popular cultures of oral tradition, particularly those of African matrix, and the cultural policies implemented in Brazil from the 2000s, which bring to the public agenda this important segment. From the psychopolitical approach of the political consciousness and participation and the critical view on the contemporary discourses around the culture as product, economic development, of the technical and managerial practice in the field of the cultural management, as well as through exploratory theoretical and conceptual applied research theoretical concepts of cultural rights, Gramscian conception of hegemony and theories of cultural reproduction and empirical research among the members of the Network of Popular and Traditional Cultures, we will analyze the impact of such policies, built in the bourgeois state. market logic and bureaucracy in access to development - in the organization and construction of the subjectivity of individuals and communities of oral tradition. Finally, we address the problem of the criteria for evaluating cultural policies, deeply marked by instrumentalization, reflecting on the adequacy of the analytical categories used to evaluate cultural processes.